Escherichia coli adhesion portion FimH functions as an adjuvant for cancer immunotherapy - Wei Zhang (Nature Portfolio, 2020)
TLR4 agonists have been proposed as immunotherapeutics in cancer. Here, the authors show the TLR4-dependent adjuvant effect of FimH, an E. coli adhesin, in promoting dendritic cell mediated-T cell activation and response to immune checkpoint blockade in preclinical cancer models.